Intestinal ulcers as an initial finding in EBV-associated lymphoproliferative disorder: A case report - Wang, Sizhu; Dai, Yinghuan; Zhang, Jie; Ou, Dalian; Ouyang, Chunhui; Lu, Fanggen (Medicine (Baltimore), 2020)
Epstein-Barr virus (EBV)-associated T-cell lymphoproliferative disorder (LPD) usually occurs in children and young adults. Gastrointestinal involvement is rare. EBV-associated T-cell lymphoproliferative disorder manifesting as intestinal ulcers poses diagnostic challenges clinically and pathologically because of the atypical manifestations. We concluded that some indicators according to our case and literatures, which might be helpful to the diagnosis of EBV-associated LPD manifested as intestinal ulcers. Here we present a 26-year-old man with complaints of diarrhea and abdominal pain that had persisted for 1 year. Multiform and multifocal deep ulcers were discovered in the colonoscopy. Cell atypia was not obvious but colitis with crypt distortion was found in pathology. According to the symptoms, laboratory examinations, colonoscopy and pathology results, Crohn Disease was diagnosed. Infliximab therapy was initiated based on the diagnosis of Crohn Disease. After the fifth course of therapy, intermittent fever and hematochezia occurred. Physical examination revealed swollen tonsils and ulcers, and purulent exudate from the right tonsil and palatoglossal arch were observed. Biopsies obtained through colonoscopy and nasopharyngoscopy demonstrated EBV-associated T-cell proliferation disease (level 3). After that, the tissue sample from the first colonoscopy was reexamined immunohistochemically. The result suggested EBV-associated T-cell proliferation disease (level 1). When we confront with patients with multiform and multifocal deep intestinal ulcers, not only the common diseases such as Crohn Disease and intestinal tuberculosis should be considered, EBV-associated T-cell proliferation disease should be considered as well. Repeated multiple biopsy, gene rearrangement, EBV DNA quantitative analysis result, EBV-encoded RNA(EBER) and experienced pathologists might be helpful to the diagnosis.